P55 Who accesses emergency hormonal contraception through an online sexual health service?. (16th June 2022) - Clune, Mark; Ebbutt, Kate; Goward, Charlotte; Perera, Sean
Abstract : Introduction: The COVID-19 pandemic has shifted services offered in clinic online, with some local authorities starting to offer Emergency Hormonal Contraception (EHC) through a sexual health e-service. After completing an online, asynchronous consultation, EHC could be delivered or collected in pharmacy. Method: Retrospective analysis of 12, 016 EHC consultations completed between 1st January 2021 and 31st December 2021, from 11 local authority areas in London. Age, ethnicity, and deprivation deciles were used to identify demographic trends. Results: The majority of EHC consultations were completed by 25-34 year olds (41.0%, n=4922). 53.4% (n=6422) of consultations were completed by users from the bottom 3 deciles of deprivation. 74.6% (n=8967) of consultation were from racially minoritised groups. Amongst 16-17 year olds and 35-44 year olds, the majority of consultations were completed by users in the bottom 3 deciles of deprivation (58.5% (n=197) and 58.6% (n=495) respectively). 66.2% (n=1289) of Black African women were from the bottom 3 deciles of deprivation, as were 58.6% (n=1498) of Black Caribbean women and 46.4% (n=1416) of White British women. 53.1% (n=1033) of Black African women, 54.3% (n1388) of Black Caribbean women, and 47.1% (n=1435) of White British women, were 16-24 years old. Discussion: The majority of individuals accessing online EHC are young and racially minoritised, experiencing significant levels of deprivation. This approach to helping users access online EHC could help reduce unintended pregnancies and mitigate health inequalities. Local authorities could consider whether an online EHC service would help in their local area.